The use of motion capture in non-realistic animation - Paiva, João Pedro Tavares Medeiros (2015)
The Use of Motion Capture in Non-realistic Animation explores the possibility of creating non-realistic animation through the use of motion capture. In this study we look to the particularities of cartoony/non-realistic animation while trying to as-certain if it is viable to create this type of animation through the process of motion capture. This dissertation will, firstly, expose the historical, theoretical, technical and artistic context. There will be a brief description of important landmarks and general overview of the history of animation. There will also be an explanation of how animators’ will to mimic real life motion, led to the invention of several technologies in order to achieve this goal. Next we will describe the several stages that compose the motion capture process. Lastly there will be a comparison be-tween key-frame animation and motion capture animation techniques and also the analysis of several examples of films where motion capture was used. Finally there will be a description of the production phases of an animated short film called Na-poleon’s Unsung Battle. In this film the majority of its animated content was obtained through the use of motion capture while aiming for a cartoony/non-realistic style of animation. There is still margin for improvement on the final results but there is also proof that it is possible to obtain a non-realistic style of animation while using motion capture technology. The questions that remain are: is it time effective and can the process be optimized for this less than common use.